Hornblende dehydration reactions during magma ascent at Soufriere Hills Volcano, Montserrat - Buckley, V; Sparks, R; Wood, B (2006)
Hornblende phenocrysts in recent andesites of the Soufrière Hills Volcano display reaction rims of microcrystalline plagioclase, pyroxene, Fe-oxides and interstitial glass, formed by decompression during magma ascent. Mass balance calculations give the following reactions with mineral proportions in agreement with modal abundances: 100.0hbl→49.8cpx+27.6opx+18.2plag+4.5Ti-mag 100.0hbl→53.9cpx+24.4opx+8.1plag+1.9ilm+1.7mag These reactions require an open chemical system with exchange of selected components with surrounding melt. Volatiles, TiO2 and alkalis are expelled and SiO2 and FeOT are consumed. Matrix glasses fall into two compositional groups. Glasses in pumice are relatively rich in CaO and poor in K2O and Na2O compared to glasses in dome samples. The former glasses formed by moderate amounts of groundmass crystallisation of plagioclase, associated with rapid magma ascent in explosive eruptions. The later glasses evolved in response to hornblende breakdown, groundmass crystallisation and mixing of melts from different levels during slow magma ascent and extended residence time in the dome. Interstitial glass compositions in reaction rims reflect the compositions of the surrounding matrix glasses, but show variable compositional differences mostly consistent with the proposed open-system reactions. © Springer-Verlag 2006.